Investigating the photophysical properties of benzophenone based TADF emitters :|a computational approach - Baş, Ekin Esme. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
In this study, several TADF and non-TADF emitters containing benzophenone or its derivatives as the electron acceptor units have been investigated by implementing computational methods. M06-2X/6-31+G(d,p) method has been used to optimize ground state (S0) and first triplet excited state (T1) geometries, and solvent effects have been taken into account implicitly. Furthermore, a wide range of TADF descriptors have been determined and investigated. Torsion angles between the donor and acceptor units have been measured to gain insight into the spatial separation of the frontier orbitals. Absorption spectra have been generated by implementing Wigner distribution to include dynamic effects. Singlet-triplet energy gaps ( EST ) have been calculated by employing Tamm-Danco Approximation (TDA). Natural transition orbitals (NTO) and S indices have been computed to examine the amount of overlap between the frontier orbitals. Lastly, spin-orbit coupling (SOC) constants have been calculated to assess the RISC possibilities. In addition to the descriptor analysis, benchmark calculations have been performed to determine the most suitable functionals with respect to experimental data. With this purpose, excited state calculations have been carried out with B3LYP, PBE0, BLYP and M06-2X functionals together with 6-31+G(d,p) basis set. The results clearly indicate that rigidity of the molecular structure and spatial separation of the frontier orbitals are the most important factors that in uence the efficiencies of the photophysical processes which cause TADF emission. The computational methods and photophysical descriptors employed in this study may contribute to the design of novel TADF materials as they reproduce well the experimental findings.
Keywords: Photochemistry.; Quantum chemistry.